2019
DOI: 10.1021/acs.jpcc.9b06761
|View full text |Cite
|
Sign up to set email alerts
|

Selective Probing of Thin-Film Interfaces Using Internal Reflection Sum-Frequency Spectroscopy

Abstract: The study of interfacial properties of thin films such as polymers is an important area of surface science. The application of visible-infrared sum-frequency generation spectroscopy to such systems requires a careful interpretation of the results, as the electric field magnitude and phase at each interface must be determined in a manner that takes thin film interference effects into account. Several schemes have been proposed for handling the local field corrections, and these methods all have their origins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…This break in inversion symmetry is what generates the SFG signal. Furthermore, the selection of the film thickness and angles of incidence restricts our probe region to the film–solution interface . A set of PDMS films was spin coated onto the surfaces of dove prisms and then subjected to the same soaking conditions (DI water and 0.9 M NaCl) as the films prepared on microscope slides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This break in inversion symmetry is what generates the SFG signal. Furthermore, the selection of the film thickness and angles of incidence restricts our probe region to the film–solution interface . A set of PDMS films was spin coated onto the surfaces of dove prisms and then subjected to the same soaking conditions (DI water and 0.9 M NaCl) as the films prepared on microscope slides.…”
Section: Resultsmentioning
confidence: 99%
“…A subset of the polymer films were soaked in either DI water (Milli-Q) or 5% wt/wt NaCl solution for 30 d. After removing the slides from the baths, the PDMS surface was rinsed with DI water and air dried for 20 min. The PDMS films for SFG experiments were spin coated at 4000 rpm for 3 min on the surface of IR-grade silica prisms using the same 10:1 ratio of base to curing agent but at a lower concentration (5% w/w PDMS in chloroform) to obtain a thickness of 370 ± 20 nm as measured by Raman spectroscopy …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a need to develop an ultrasensitive technique which could be used to study the distribution of ultrathin silicone oil layers on surfaces. In recent decades, second-order nonlinear optical spectroscopic techniques such as sum frequency generation (SFG) vibrational spectroscopy and second-harmonic generation (SHG) have been applied to study molecules (including proteins) on surfaces and at interfaces. Such research demonstrated that second-order nonlinear optical spectroscopic techniques are very promising in detecting monolayer and even submonolayer molecules at interfaces in situ. SFG has been applied to examine the molecular structures of surfaces and interfaces involving solid silicone and silicone oil to understand important interfacial properties such as adhesion, friction, antifouling, and fouling release. In particular, SFG has been applied to study thin films of silicone on water surfaces . SFG provides chemical and orientational information on the molecular structure of chemical groups at interfaces.…”
Section: Introductionmentioning
confidence: 99%